2022
DOI: 10.3390/su14105868
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Factors That Affect Consumers’ Purchase Intention of Organic Food Products in a Developing Country

Abstract: The purpose of this article is to investigate the factors that influence consumers’ intention to purchase organic food in Egypt. Given the novelty of organic food marketing in developing countries, much of the factors that influence its consumption are still inadequately explored in the marketing literature. A conceptual model of the factors that impact the consumption of organic food was developed based on the theory of planned behaviour and previous literature in the area of food consumption. To test the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 76 publications
8
53
0
2
Order By: Relevance
“…Additionally, the results of our study suggest that subjective norms failed to have a significant influence on continuous purchase intention for organic food. These findings are in line with other previous investigations [ 36 , 37 ] and also reinforced the arguments of the debated or poor role of subjective norms in different contexts [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, the results of our study suggest that subjective norms failed to have a significant influence on continuous purchase intention for organic food. These findings are in line with other previous investigations [ 36 , 37 ] and also reinforced the arguments of the debated or poor role of subjective norms in different contexts [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, other researchers [ 21 , 34 ] have argued for the effectiveness of subjective norms when justifying consumers’ food options and have suggested that further research is needed. Previous scholars observed an unfavourable correlation between subjective norms and green purchase intention [ 35 , 36 ]. Asih et al [ 37 ] claimed that there is no significant relationship between subjective norms and interest in using green products.…”
Section: Theoretical Framework and Development Of Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Buyers not only communicate with relatives and friends, but are also keen to obtain information from online sources. With maternal and infant groups, the WeChat Public Platform, maternity and infant apps, and short video platforms, sharing information makes the interaction between consumer groups more obvious [54,55].…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…Strategies that analyse customer satisfaction are focused on the role played by organisations and destinations in providing the service or making the product (Neuhofer et al 2013, Robina-Ramírez et al 2021aHo et al 2021). This role is enriched from the potential decision-making and motivating power of the tourist who adds value to the product or service (Prebensen et al 2013;Tan et al 2016); indeed, the client goes from being a mere recipient of a service to a cocreator of value (Yi and Gong 2013;Zayed et al 2022).…”
Section: Introductionmentioning
confidence: 99%